Students with Disabilities’ Access to Distance Education: : A Case for Transformational Leadership within the Ambit of Ubuntu - Aluko, Folake Ruth; Mampane, Motlalepule Ruth (International Journal of African Higher Education, 2022)
There has been much debate on access and social justice, and the role of distance education in redressing social injustices. However, little is known about these issues in relation to students with disabilities. The South African Department of Higher Education and Training’s Strategic Policy Framework on Disability for the Post-School Education and Training System aims to improve people with disabilities' access to and success in post-school education and training. The document notes that despite the ground gained in transforming the the country's higher education landscape, systematic, institutional and personal challenges persist in relation to integrating such students into postschool education and training. This article highlights the challenges typically encountered by students with disabilities despite policy responses and why these have not worked. It proposes transformational leadership nestled within Ubuntu to transform the issue of disability in post-school education and training and offers directions for further research directions. Key words: distance education; disability; access, social justice; Ubuntu; transformational leadership